Photocatalytic Degradation of Commercial Diazinon Pesticide Using C,N-codoped TiO2 as Photocatalyst - Khoiriah Khoiriah; Diana Vanda Wellia; Jarnuzi Gunlazuardi; Safni Safni (Indonesian Journal of Chemistry, 2020)
Diazinon (C12H21N2O3PS) is an effective pest controller that has been frequently used by farmers in agriculture. It is a nonspecific and highly toxic pesticide having low persistence in the environment and categorized as moderately hazardous class II. The degradation of commercial diazinon in aqueous solution was investigated by photocatalysis using low-energy activated C,N-codoped TiO2 as catalyst under visible-light. The influence of some parameters, i.e., catalyst concentration, the initial concentration of diazinon, initial pH of diazinon, and irradiation time on the diazinon degradation was studied. The amount of diazinon degradation was strongly influenced by all the above parameters. The results show that titania-modified enhanced the degradation percentage of diazinon, from 44.08% without a catalyst to 86.93% by adding 12 mg C,N-codoped TiO2 catalyst after 30 minutes visible-light irradiation. UV-visible spectrophotometer, HPLC, and COD analysis verified that diazinon was successfully degraded under photocatalysis visible.